Preparation and electrochemical performance of VO2(A) hollow spheres as a cathode for aqueous zinc ion batteries. Issue 60 (30th October 2019) - Li, Runxia; Yu, Xin; Bian, Xiaofei; Hu, Fang
Abstract : VO2 (A) hollow spheres exhibit superior zinc ion storage performance, large reversible capacity of 357 mA h g −1 at 0.1 A g −1, and good cycling stability with a capacity retention of 76% over 500 cycles at 5 A g −1 Abstract : Rechargeable aqueous zinc ion batteries (ZIBs), owing to their low-cost zinc metal, high safety and nontoxic aqueous electrolyte, have the potential to accelerate the development of large-scale energy storage applications. However, the desired development is significantly restricted by cathode materials, which are hampered by the intense charge repulsion of bivalent Zn 2+ . Herein, the as-prepared VO2 (A) hollow spheres via a feasible hydrothermal reaction exhibit superior zinc ion storage performance, large reversible capacity of 357 mA h g −1 at 0.1 A g −1, high rate capability of 165 mA h g −1 at 10 A g −1 and good cycling stability with a capacity retention of 76% over 500 cycles at 5 A g −1 . Our study not only provides the possibility of the practical application of ZIBs, but also brings a new prospect of designing high-performance cathode materials.